A Model Combining Psychotherapy with Spirituality and Religion in the area of Palliative Care and Bereavement - Chase, Benna (European Journal for Qualitative Research in Psychotherapy, 2012)
This paper presents a Model for working with the dying and the bereaved within the Maltese context arising from my years of prac- tice in oncology and palliative care. The use of self is an important element. Self, from a Gestalt perspective, indicates cohesion over time – Integrity, and openness to change at the contact boundary – Growth (Yontef, 1993), two important characteristics in the Model. The interplay between the psychotherapeutic and the spiritual and religious is addressed, within a culture where the Roman Catholic Religion is a dominant tradition. The Model advocates that, apart from practising presence and inclusion, a practitioner needs to be prepared to stay with the client in the long space between Withdrawal and Sensation, with its dearth of figure-formation. This requires a deep level of conviction that sustains the practitioner in the ‘between’ to allow a natural, positive figure to emerge, with the resulting growth of both practitioner and client.